Dr. Peter Scardino's prostate book : the complete guide to overcoming prostate cancer, prostatitis, and BPH - Scardino, Peter (New York : Avery Publishing Group, 2006)
A guide to understanding and overcoming three key prostate health problems counsels readers on how to prevent disease, interpret complicated test results, become informed about the range of available treatments, and preserve sexual intimacy.
pt. 1. The prostate and the normal male -- 1. The prostate -- 2. Normal male function -- 3. Changes with aging -- pt. 2. Common prostate problems -- 4. Prostatitis -- 5. BPH (prostate enlargement) -- pt. 3. Prostate cancer -- 6. Prostate cancer facts -- 7. Risk factors and prevention -- 8. Detecting prostate cancer with PSA and other tests -- 9. Biopsy -- 10. Understanding your cancer -- 11. Understanding yourself -- 12. Deciding how to treat localized prostate cancer -- 13. Watchful waiting -- 14. Surgery -- 15. Radiation therapy -- 16. Other local therapies -- 17. Urinary side effects -- 18. Sexual side effects -- 19. Bowel side effects -- 20. Rising PSA after surgery or radiation therapy -- 21. Treating metastatic prostate cancer.
Keywords: PROSTATE DISEASES